An Outbreak of Canine Distemper Virus in Tigers (Panthera tigris): Possible Transmission from Wild Animals to Zoo Animals - NAGAO, Yumiko; NISHIO, Yohei; SHIOMODA, Hiroshi; TAMARU, Seiji; SHIMOJIMA, Masayuki; GOTO, Megumi; UNE, Yumi; SATO, Azusa; IKEBE, Yusuke; MAEDA, Ken (Journal of Veterinary Medical Science, 2012)
Canine distemper virus (CDV), a morbillivirus that causes one of the most contagious and lethal viral diseases known in canids, has an expanding host range, including wild animals. Since December 2009, several dead or dying wild raccoon dogs (Nyctereutes procyonoides) were found in and around one safari-style zoo in Japan, and CDV was isolated from four of these animals. In the subsequent months (January to February 2010), 12 tigers (Panthera tigris) in the zoo developed respiratory and gastrointestinal diseases, and CDV RNA was detected in fecal samples of the examined tigers. In March 2010, one of the tigers developed a neurological disorder and died; CDV was isolated from the lung of this animal. Sequence analysis of the complete hemagglutinin (H) gene and the signal peptide region of the fusion (F) gene showed high homology among these isolates (99.8-100%), indicating that CDV might have been transmitted from raccoon dog to tiger. In addition, these isolates belonged to genotype Asia-1 and had lower homology (<90%) to the vaccine strain (Onderstepoort). Seropositivity of lions (Panthera leo) in the zoo and wild bears (Ursus thibetanus) captured around this area supported the theory that a CDV epidemic had occurred in many mammal species in and around the zoo. These results indicate a risk of CDV transmission among many animal species, including large felids and endangered species.